Thermodynamic analysis of an innovative liquid desiccant air conditioning system to supply potable water. (15th September 2017) - Ahmed, M.A.; Gandhidasan, P.; Zubair, Syed M.; Bahaidarah, Haitham M.
Highlights: The study objective is to reduce the energy consumption of desiccant AC system. Heat and mass losses are recovered in the proposed system using a condenser. The conventional and the proposed systems are compared in terms of COP. The proposed system performance is better than the conventional system. The proposed system produces freshwater in addition to space cooling. Abstract: Liquid desiccant air conditioning systems are cost-effective, environmentally friendly and energy efficient techniques, especially in coastal areas. In the conventional liquid desiccant air conditioning system, the scavenging air is expelled into the atmosphere carrying a considerable amount of energy and water vapor. Thus, there is plenty of room to improve the system performance by recovering these losses. The proposed system consists of a conventional liquid desiccant air conditioning system plus a condenser. The aim of this study is to reduce the energy consumption by recovering the heat from the scavenging air using the condenser while also producing freshwater in addition to space cooling. Lithium chloride (LiCl) is used as the liquid desiccant for this study. The mathematical formulation for simultaneous heat and mass transfer between the condenser and the regenerator was developed to establish a comparison between the performance of the conventional and modified systems. Using the generated model, it is found that the modified system performance is 11.25% better than the conventional system and that it produces 86.4 kg of freshwater per hour as a by-product under the given conditions.